Application of high throughput pretreatment and co‐hydrolysis system to thermochemical pretreatment. Part 2: Dilute alkali. Issue 11 (10th June 2013) - Li, Hongjia; Gao, Xiadi; DeMartini, Jaclyn D.; Kumar, Rajeev; Wyman, Charles E.
ABSTRACT High throughput pretreatment (HTPH) and enzymatic hydrolysis systems are now vital for screening large numbers of biomass samples to investigate biomass recalcitrance over various pretreatment and enzymatic hydrolysis conditions. Although hydrothermal pretreatment is currently being employed in most high throughput applications, thermochemical pretreatment at low and high pH conditions can offer additional insights to better understand the roles of hemicellulose and lignin, respectively, in defining biomass recalcitrance. Thus, after successfully applying the HTPH approach to dilute acid pretreatment [Gao et al. (2012) Biotechnol. Bioeng. 110(3): 754–762], extension to dilute alkali pretreatment was also achieved using a similar single‐step neutralization and buffering concept. In the latter approach, poplar and switchgrass were pretreated with 1 wt% sodium hydroxide at 120°C for different reaction times. Following pretreatment, an H2Cit−/HCit2− buffer with a pH of 4.5 was used to condition the pretreatment slurry to a pH range of 4.69–4.89, followed by enzymatic hydrolysis for 72 h of the entire mixture. Sugar yields showed different trends for poplar and switchgrass with increases in pretreatment times, demonstrating the method provided a clearly discernible screening tool at alkali conditions. This method was then applied to selected Populus tremuloides samples to follow ring‐by‐ring sugar release patterns. Observed variations were compared to results from hydrothermal pretreatments, providing new insights in understanding the influence of biomass structural differences on recalcitrance. Biotechnol. Bioeng. 2013;110: 2894–2901. © 2013 Wiley Periodicals, Inc.